Intestinal stomas. Issue 1 (January 2023) - Pine, James; Stevenson, Lynn; On, Jason
Abstract: The formation of an intestinal stoma (usually ileostomy or colostomy) is an integral part of the surgical management of several pathologies of the gastrointestinal tract – in both emergency and elective patients. The basic underlying principle is that faecal flow is diverted from the site of the pathology by bringing the end or a loop of bowel through the anterior abdominal wall. A stoma may be created in a temporary or permanent role to reduce morbidity and mortality associated with several conditions of the gastrointestinal tract including perforation, inflammatory bowel disease, bowel obstruction and elective cancer operations. Early complications of stoma formation include ischaemic necrosis of the stoma, stomal retraction and obstruction with later potential complications of parastomal hernia formation, stomal prolapse and peristomal skin changes.